2020
DOI: 10.1002/mgg3.1504
|View full text |Cite
|
Sign up to set email alerts
|

Genomic study of dilated cardiomyopathy in a group of Mexican patients using site‐directed next generation sequencing

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Previous studies with patients fulfilling DCM diagnostic criteria have observed an overall diagnostic yield of 19%–47% ( 11 , 12 , 15 , 20 ). In the recent ESC EURObservational Research Programme (EORP) Cardiomyopathy Registry study 33% of the patients had a diagnostic variant ( 13 ).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies with patients fulfilling DCM diagnostic criteria have observed an overall diagnostic yield of 19%–47% ( 11 , 12 , 15 , 20 ). In the recent ESC EURObservational Research Programme (EORP) Cardiomyopathy Registry study 33% of the patients had a diagnostic variant ( 13 ).…”
Section: Discussionmentioning
confidence: 96%
“…53 47 ) with mutations in ACTC1. Of the hundreds of individuals described with ACTA1associated myopathy, only twelve (nine unique variants) [57][58][59][60][61][62][63][64][65] have been reported to also have a cardiac abnormality (Table S1), either in conjunction with a skeletal myopathy (N=10) or alone (N=2). Rare variants in ACTC1 resulting in congenital contractures in a small fraction of persons with ACTC1 variants appears to be the corollary.…”
Section: Discussionmentioning
confidence: 99%
“…One HCM case was associated with congenital myopathy with the core, whereas for another, the myopathy was unclassified (Kaindl et al, 2004 ). Likewise, two cases were associated with DCM alone (Carnevale et al, 2020 ; Reza et al, 2018 ). Genotype–phenotype correlation has not been elucidated; however, 327–328 AA and 336–338 AA residues in the ACTA1 sequence might accumulate mutations related to cardiomyopathy (Figure 2b,c ).…”
Section: Discussionmentioning
confidence: 99%